How employers use signals of cognitive and noncognitive skills at labour market entry : insights from field experiments - Protsch, Paula [Verfasser]; Solga, Heike [Verfasser] (My University, 2015)
"This article aims to improve our understanding about why and how individuals' signals of cognitive and noncognitive skills influence labour market outcomes. We study how employers use skills signals when hiring labour market entrants. These demand-side microprocesses are investigated at the apprenticeship market in Germany, which functions as the main entry labour market below tertiary-level education. Qualitative studies and personnel psychology research suggest multistage hiring processes. We concentrate on the first stage at which employers narrow the applicant pools based on written application documents. Their information is limited to applicants' school reports - including their grades (as signals of cognitive skills) and teachers' evaluations of their behaviours (as signals of noncognitive skills). We conducted two linked field experiments, applying the correspondence test method. Analysing the unbiased employers' responses to randomly varied fictitious applicant profiles enables us to discover whether, and if so how, applicants' skills signals are used as 'screens' at the first selection stage. The experiments reveal that both skills signals are important selection criteria, but employers prefer noncognitive skills signals. Moreover, the findings confirm that firms use thresholds (cut-off values) for selection criteria instead of linear rankings." (Authors' abstract, BIBB-Doku)

Dieser Beitrag untersucht, warum und in welcher Weise Fächernoten als Signal für kognitive und Lehrerbewertungen zum Sozialverhalten als Signal für nicht-kognitive Fähigkeiten die individuellen Erfolgsaussichten bei Bewerbungen um einen Ausbildungsplatz beeinflussen. In einem Feldexperiment wurden 322 Bewerbungen auf reale Stellenanzeigen für die Berufe Mechatroniker, Automechaniker und Elektriker im Namen von fiktiven männlichen Zehntklässlern, die vor dem mittleren Schulabschluss stehen, verschickt. Im Ergebnis zeigte sich ein starker Einfluss von Kopfnoten. So war die Erfolgsquote (Einladung zu einem Vorstellungsgespräch) von den Bewerbern mit einem Notenschnitt von 3,4 und positiven Verhaltensbewertungen etwa doppelt so hoch wie die jener Bewerber, die zwar einen Fächerdurchschnitt von 3,0, aber nur unvorteilhafte Beurteilungen zum Arbeits- und Sozialverhalten vorweisen konnten. Den klassischen Fächernoten wird damit die Bedeutung jedoch nicht abgesprochen, da gute Verhaltensbewertungen schlechte Fächernoten nicht vollständig kompensieren können. (BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; L 8 Diagnostik / Eignung; S 5.3 Personalentwicklung; S 3.2 Unternehmen und Behörden; Ausbildungschance; Betriebliche Berufsausbildung; Ausbildungsstellenbewerber; Altbewerber; Bewerberauswahl; Auswahlverfahren; Einflussfaktor; Schulleistung; Sozialkompetenz; Empirische Untersuchung